Dialogue strategies with estrangement in the beginning of university life home and permanence policies at the federal University of Southern Bahia - Ferreira, Sandro Augusto Silva (Universidade Estadual de Campinas, 2017)
Recent changes in the Public University, especially as the admission policies through Affirmative Action, generate a set of challenges in promoting material and symbolic stay at the university. In addition to student assistance programs aimed at monetary support has a new set of interventions aimed at the reception and production of affiliation become necessary for new students, mostly from families with no history of university education. In this sense the reception activities and guidance in the early days, and Deeds to combat hazing and other violence plays an important role in building successful careers in college. This article evaluates, by means of an experience report, the model adopted by the Federal University of Southern Bahia at home to students of their second class. It also assesses the potential of this affiliation mechanism for the success of the variousaffirmative action programs.